2023
DOI: 10.3390/gels9060476
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Alginate—PVA Ratio and the Addition of Bioactive Substances on the Performance of Hybrid Hydrogel Membranes as Potential Wound Dressings

Abstract: Healthcare professionals face an ongoing challenge in managing both acute and chronic wounds, given the potential impact on patients’ quality of life and the limited availability of expensive treatment options. Hydrogel wound dressings offer a promising solution for effective wound care due to their affordability, ease of use, and ability to incorporate bioactive substances that enhance the wound healing process. Our study aimed to develop and evaluate hybrid hydrogel membranes enriched with bioactive componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…The combination of natural and synthetic polymers in the production of wound dressings leads to a synergistic effect that enhances the material’s properties [ 72 ]. As shown in our previous work, polymer type, concentration, and the addition of bioactive compounds have the potential to significantly impact the properties of hydrogel membranes [ 60 ]. In this study, a combination of alginate and polyvinyl alcohol (PVA) was employed, alongside the inclusion of bioactive compounds like collagen and hyaluronic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of natural and synthetic polymers in the production of wound dressings leads to a synergistic effect that enhances the material’s properties [ 72 ]. As shown in our previous work, polymer type, concentration, and the addition of bioactive compounds have the potential to significantly impact the properties of hydrogel membranes [ 60 ]. In this study, a combination of alginate and polyvinyl alcohol (PVA) was employed, alongside the inclusion of bioactive compounds like collagen and hyaluronic acid.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that preventing protein denaturation by medicinal agents in vitro indicates an anti-inflammatory effect. The assays used BSA as a model protein and aspirin as a positive control, and determinations were performed at 280 nm [ 60 ]. It was observed that all hydrogel formulations present an anti-inflammatory activity, protecting BSA from denaturation ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation